Comparison of Fitness Levels and Participation in Physical Education Learning Between PPLP Athletes Rowing West Java Students and Non-Athletes - Anisa Shopiani; Sufyar Mudjianto (UNIVERSITAS NEGERI MAKASSAR, 2022)
The purpose of this study was to measure the level of fitness and participation of students in physical education learning between athletes and non-athletes (regular) at SMA Negeri 2 Padalarang. This research uses quantitative research methods, with ex post facto research. The samples in this study were 10 PPLP rowing students and 10 non-athlete students (regular) with sampling techniques using Census Sampling (Saturated Sampling) and Purposive Sampling. The research instrument used TKJI and questionnaires in the data and analyzed using the t-test. The result is that Paddle PPLP students have a more significant impact on their fitness levels and participation in physical education learning. Based on these results, it can be concluded that education can be used as an alternative to increasing the level of fitness and participation of students.